Displacement-based design approach to evaluate the behaviour factor for multi-storey CLT buildings. (15th December 2019) - Hummel, Johannes; Seim, Werner
Highlights: New procedure to evaluate the behaviour factor for CLT structures. Results of Experimental investigations on connections and wall elements. Derivation and validation of properties of nonlinear springs. Development of reference structures and consistent structural models for CLT. Performing nonlinear static (pushover) analyses. Application of displacement-based design (DBD) to CLT structures. Confirmation of a behaviour factor for the CLT construction by DBD. Abstract: Different aspects of force-based and displacement-based design of multi-storey cross-laminated timber (CLT) structures are discussed in the context of the definition of the behaviour factor q . A review of approaches to determine the behaviour factor for force-based design will be given. A new approach to evaluate the behaviour factor based on non-linear static analyses together with a displacement-based design procedure will be discussed and demonstrated. CLT structures with two and four storeys and different types of structural models are considered for illustration and validation. Results of experimental investigations on anchoring connections will be presented. These test data are employed to derive properties of non-linear springs for structural modelling. The spring properties will be validated by comparison of analytical to experimental results on the wall level. An appropriate behaviour factor can be found based on the evaluation of 24 different structural configurations.